Beyond experience: how customer engagement transforms AI interactions into Generation Z loyalty - Sri Mona Octafia; Dina Hadia; Annisa Weriframayeni; Rio Andika Malik; Vicky Setia Gunawan (Universitas Muhammadiyah Enrekang, 2025)
The use of Artificial Intelligence (AI) in customer service, including chatbots, personalized recommendations, and virtual assistants, has significantly improved service efficiency and customer experience. However, how these AI-enabled experiences translate into long-term customer loyalty is still not fully understood, especially among Generation Z, who expect digital interactions to be efficient, authentic, and engaging. Previous studies indicate that customer engagement—reflecting cognitive, emotional, and behavioral involvement—may play an important mediating role, yet empirical evidence in emerging market contexts such as Indonesia remains limited. This study aims to examine the mediating role of customer engagement in the relationship between AI-enabled experience and sustainable loyalty among Generation Z consumers in Padang City, Indonesia. Using a quantitative cross-sectional survey design, data were collected from Generation Z respondents who had interacted with AI-based services in the last six months. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test both direct and indirect relationships among variables. The results indicate that AI-enabled experience has a positive and significant effect on sustainable loyalty, both directly and indirectly through customer engagement. AI-enabled experience significantly influences customer engagement, which in turn strongly affects sustainable loyalty, confirming the partial mediating role of engagement. These findings highlight that AI-driven services should be designed not only for efficiency but also to foster active interaction and engagement in order to build long-term loyalty among Generation Z consumers.